2020
DOI: 10.1007/s11325-020-02113-1
|View full text |Cite
|
Sign up to set email alerts
|

A detection dog for obstructive sleep apnea: could it work in diagnostics?

Abstract: Purpose We have previously demonstrated that dogs can be trained to distinguish the urine of patients with obstructive sleep apnea (OSA) from that of healthy controls based on olfaction. Encouraged by these promising results, we wanted to investigate if a detection dog could work as a screening tool for OSA. The objective of this study was to prospectively assess the dogs’ ability to identify sleep apnea in patients with OSA suspicion. Methods Urine samples were collected from 50 patients suspected of having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several studies of dogs' ability to detect disease have reported individual differences in performance between dogs (8,(22)(23)(24)(25)(26)(27). Due to the time investment required for training, it is also common practice to re-use detection dogs across multiple studies (28)(29)(30)(31)(32)(33)(34). However, there is a lack of knowledge about how changing training procedures and sample sources could affect performance in a subsequent study.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of dogs' ability to detect disease have reported individual differences in performance between dogs (8,(22)(23)(24)(25)(26)(27). Due to the time investment required for training, it is also common practice to re-use detection dogs across multiple studies (28)(29)(30)(31)(32)(33)(34). However, there is a lack of knowledge about how changing training procedures and sample sources could affect performance in a subsequent study.…”
Section: Introductionmentioning
confidence: 99%